Occurrence and mass loads of biocides in plastic debris from the Pearl River system, South China. (May 2020) - Jia, Yu-Wei; Huang, Zheng; Hu, Li-Xin; Liu, Shan; Li, Heng-Xiang; Li, Jin-Ling; Chen, Chang-Er; Xu, Xiang-Rong; Zhao, Jian-Liang; Ying, Guang-Guo
Abstract: Chemical pollution in the plastic debris is an increasing global concern as most pollutants might transfer from the environment to living organisms via plastic debris. In this study, biocides in the plastic debris floating on the surface water of the Pearl River system were investigated. The abundances of large plastic debris and microplastics in the surface water were 0.07 ± 0.13 and 0.94 ± 1.87 items/m 3, respectively. Totally, 15 and 16 out of 19 biocides were detected in the large plastic debris and microplastics, with the concentration of each biocide in the ranges of 22.6–2460 ng/g and 16.9–2890 ng/g, respectively. Meanwhile, the concentration ranges of the detected biocides were 0.01–215 ng/L in surface water. Triclosan, triclocarban, methylparaben, and N, N -diethyl-3-methylbenzamide (DEET) were the frequently detected compounds in the plastic samples and surface water. The partition coefficients ( K d ) of biocides between the plastic debris and surface water showed a weak positive correlation with K ow values. Biocides were also detected on the natural floats (tree leaves and branches) at concentrations of 13.7–786 ng/g. The annual mass load of biocides in plastic debris at each site was up to 265 g/y, thereby suggesting that plastic debris might be an important carrier for the emerging contaminants, such as biocides. Graphical abstract: Image 1 Highlights: Biocides adsorbed in the plastic debris and natural floats were investigated in the Pearl River system. 16 biocides were detected at once in the plastic debris with the concentrations up to 2890 ng/g in microplastics. Triclosan, triclocarban, DEET, methylparban and climbazole showed high adsorption abilities for plastics. Plastic debris might be an important carrier for biocides.